Oral mini-pulse steroid therapy in severe chronic urticaria - Mohammad Abid Keen; Faizan Younus Shah (Our Dermatology Online, 2021)
Background: Treatment of chronic urticaria can be difficult at times. The present study aimed to evaluate the efficacy of oral mini-pulse (OMP) therapy with methylprednisolone in management of severe chronic urticaria (CU). Methods and material: 100 patients with severe chronic urticaria, not controlled with maximum dose of a second generation antihistamine, were enrolled in the study after an informed written consent. All patients were treated with methylprednisolone 16 mg tablet on two consecutive days of a week for 2 months along with levocetirizine 5 mg tablet once daily. All patients were reviewed at 0, 2, 4, and 8 weeks with urticaria activity score (UAS). Results: The study comprised of 100 patients (33 males and 67 females) with severe chronic urticaria. 29 patients (29%) had raised TSH levels while Autologous Serum Skin Test was positive in 37 patients. Mean UAS in patients treated with OMP was 5.76 at baseline which reduced to 0.6 at the end of treatment period. Conclusion: Mean UAS showed a significant decline following OMP therapy with methylprednisolone. Most of the patients maintained the benefits of therapy at the end of follow up period of 4 months.